LDHA-induced histone lactylation mediates the development of osteoarthritis through regulating the transcription activity of TPI1 gene - Junfeng Xia; Zongrui Qiao; Xiao Hao; Yin Zhang (Autoimmunity)
Osteoarthritis (OA) is a worldwide joint disease, leading to the physical pain, stiffness, and even disability. Lactate dehydrogenase A (LDHA) is known as a lactylation mediator that can regulate histone lactylation of its target genes. However, the role of LDHA-mediated histone H3 lysine 18 lactylation (H3K18la) in OA progression is yet to be clarified. Our study aims at revealing the role and mechanism of LDHA-mediated histone lactylation in the glycolysis of chondrocytes. In this study, we determined at first that the H3K18la level was enhanced in OA. Energy metabolism such as glycolysis is often altered in OA progress. Therefore, we further explored the mechanism mediating glycolysis and thus promoting OA progress. Moreover, glycolysis was enhanced in LPS-induced OA cell model, as evidenced by the increased glucose consumption and lactate production. Furthermore, we silenced LDHA for loss-of-function assays. The results showed that knockdown of LDHA suppressed glycolysis of LPS-induced chondrocytes. In vivo animal study demonstrated that knockout of LDHA recovered cartilage injury of OA mice. Mechanistically, we uncovered that LDHA-mediated H3K18la in TPI1 promoter enhanced the transcription activity of TPI1. Mutation of K69 site was found to ameliorate LPS-induced glycolysis in OA cell model. In conclusion, our study reveals the role of LDHA-mediated H3K18la of TPI1 promoter in OA progress.